Legal Analysis of Child Exploitation in Prostitution Practices: Human Rights Perspective and Its Implications in the Indonesian Legal System - ZAIDAN, Gathan Elang; FRELIK, Frelik; SIDIQ, Jafar (Indonesia Strategic Sustainability, 2025)
Exploitation of children in prostitution is not only a serious human rights violation, but also a reflection of systemic failure to create effective social and legal protection. This phenomenon continues to grow amid economic pressures, patriarchal norms, and weak law enforcement. Although the government has ratified the Convention on the Rights of the Child and passed the Child Protection Law, cases of child exploitation in prostitution are still rampant due to the weak integration between regulation and implementation. This study aims to evaluate the extent to which the Indonesian legal system is able to respond to the challenges of child exploitation in prostitution through a human rights perspective. Using normative legal methods and a critical approach, this study analyzes various legal policies, secondary data, and literature that discuss the root causes of child exploitation. This study also evaluates the role of state institutions and non-state actors in creating a comprehensive child protection system. The results of the study indicate that child exploitation in prostitution is not only influenced by weak legal institutions, but also by systemic socio-economic inequality. Minimal law enforcement, a culture of impunity, and stigmatization of victims worsen the situation. Furthermore, the absence of a structured rehabilitation program indicates that child protection in Indonesia has not been directed at restoring the basic rights of victims. This article recommends comprehensive reforms, including economic empowerment for vulnerable families, community education to eliminate stigma, and strengthening law enforcement and regulatory oversight institutions.